Effect of Nonspecific Chronic Low Back Pain on Walking Economy: An Observational Study - Carvalho, Alberito Rodrigo; Ribeiro Bertor, Welds Rodrigo; Briani, Ronaldo Valdir [UNESP]; Zanini, Gabriela Matte; Silva, Ligia Inez; Andrade, Alexandro; Peyre-Tartaruga, Leonardo Alexandre (Routledge Journals, Taylor & Francis Ltd, 2016)
The authors investigated the effects of chronic low back pain (LBP) and walking speed (WS) on metabolic power and cost of transport (CT). Subjects with chronic nonspecific LBP (LBP group [LG]; n = 9) and healthy (control group [CG]; n = 9) were included. The test battery was divided into 3 blocks according to WS as follows: preferred self-selected speed (PS), and lower and higher than the PS. In each block, the volunteers walked 5min, during which oxygen consumption was measured. Although without differences between groups, the LG had CT lower in slower speeds than in faster speeds. Walking speed affected CT only in the LG, which the group had the greatest walking economy at slower speeds.
Keywords: low back pain; human locomotion; walking